2017
DOI: 10.1111/bph.13825
|View full text |Cite
|
Sign up to set email alerts
|

Protein S‐sulfhydration by hydrogen sulfide in cardiovascular system

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 87 publications
1
62
0
1
Order By: Relevance
“…In the last years, it is becoming increasingly clear that also protein S-sulfuration [19] represents an important mechanism of regulation of protein activity mediated by hydrogen sulfide (H 2 S) ( Figure 1). In this respect, it has been reported that these modifications occur on enzymes, receptors, transcription factors, and ion channels and represent key regulatory events in maintaining the physiological function of proteins in the cardiovascular system [20]. Among the abovementioned reversible reactions, protein S-thiolation by LMW thiols is the most biologically…”
Section: Protein Sulfhydryls Oxidation and Atherosclerosismentioning
confidence: 99%
“…In the last years, it is becoming increasingly clear that also protein S-sulfuration [19] represents an important mechanism of regulation of protein activity mediated by hydrogen sulfide (H 2 S) ( Figure 1). In this respect, it has been reported that these modifications occur on enzymes, receptors, transcription factors, and ion channels and represent key regulatory events in maintaining the physiological function of proteins in the cardiovascular system [20]. Among the abovementioned reversible reactions, protein S-thiolation by LMW thiols is the most biologically…”
Section: Protein Sulfhydryls Oxidation and Atherosclerosismentioning
confidence: 99%
“…S-sulfhydration was performed as described previously (Meng, Zhao, Xie, Han, & Ji, 2018). Briefly, NRCMs or heart tissues were homogenized in HEN buffer (composition; 250-mM HEPES-NaOH, pH 7.7: 1-mM EDTA; 0.1-mM neocuproine), supplemented with 100-mM deferoxamine and centrifuged at 13,000× g for 30 min at 4°C.…”
Section: S-sulfhydration Assaymentioning
confidence: 99%
“…H2S has been recently demonstrated to posttranslational modification of proteins by the formation of a persulfide (-SSH) bond with the reactive cysteine residues of target proteins, termed as Ssulfhydration. After S-sulfhydration, proteins change their original function, serving as important switchers or regulators [48]. It is important to note that H2S induces Ssulfhydration on cysteine thiols under oxidation conditions.…”
Section: Discussionmentioning
confidence: 99%